(untitled) (Web of Teachers: Inderscience Research, 2025)
Knowing the characteristics of both languages implies thoroughly studying the original text, working on its vocabulary and cultural references, which is very important for the translator. This also, to some extent, requires the translator to be a scholar and a researcher.